2014
DOI: 10.3390/rs61110947
|View full text |Cite
|
Sign up to set email alerts
|

From Remotely Sensed Vegetation Onset to Sowing Dates: Aggregating Pixel-Level Detections into Village-Level Sowing Probabilities

Abstract: Abstract:Monitoring the start of the crop season in Sahel provides decision makers with valuable information for an early assessment of potential production and food security threats. Presently, the most common method for the estimation of sowing dates in West African countries consists of applying given thresholds on rainfall estimations. However, the coarse spatial resolution and the possible inaccuracy of these estimations are limiting factors. In this context, the remote sensing approach, which consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…While numerous methods have been proposed to detect the timing of vegetation green-up, maturity, senescence, and dormancy (e.g., Zhang et al, 2003;Funk and Budde, 2009), only a few have related phenological information derived from RS time series to determine actual sowing dates (e.g. Marinho et al, 2014;Jain et al, 2016;Boschetti et al, 2017;Manfron et al, 2017).…”
Section: Factors Affecting Crop Lodgingmentioning
confidence: 99%
“…While numerous methods have been proposed to detect the timing of vegetation green-up, maturity, senescence, and dormancy (e.g., Zhang et al, 2003;Funk and Budde, 2009), only a few have related phenological information derived from RS time series to determine actual sowing dates (e.g. Marinho et al, 2014;Jain et al, 2016;Boschetti et al, 2017;Manfron et al, 2017).…”
Section: Factors Affecting Crop Lodgingmentioning
confidence: 99%
“…Estimation of crop phenological metrics using RS data depends largely on greenness information captured by optical satellite sensors. Studies have found that remotely sensed crop phenological metrics, especially the start of growing season (SOS, green-up date), can provide spatially explicit information on crop development stages, including the seeding date [7,12,13]. Crop phenological metrics are usually derived from time-series vegetation indices (VIs) through curve fitting, and the indices are usually calculated from reflectance data in the visible and near-infrared (NIR) bands.…”
Section: Introductionmentioning
confidence: 99%
“…This agrometeorological approach is highly dependent on the availability of nearby weather stations, while in reality station networks tend to be quite sparse, and the estimation of crop development stages is poor over areas where there are no nearby weather stations. In this case, the estimated crop development stage is insufficient for field-scale crop modelling and management over large areas [12,34].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing, particularly the use of optical satellite imagery, has become an emerging tool for monitoring phenological events of crops at regional to national scales [3][4][5]. Sensors, such as the Advanced Very High Resolution Radiometer (AVHRR) and the Moderate Resolution Imaging relationships and model-based crop phenology [27], but have not yet been used for validation of satellite-derived phenometrics.…”
Section: Introductionmentioning
confidence: 99%